Equine Adipose-Derived Mesenchymal Stromal Cells Release Extracellular Vesicles Enclosing Different Subsets of Small RNAs. (18th March 2019) - Capomaccio, Stefano; Cappelli, Katia; Bazzucchi, Cinzia; Coletti, Mauro; Gialletti, Rodolfo; Moriconi, Franco; Passamonti, Fabrizio; Pepe, Marco; Petrini, Stefano; Mecocci, Samanta; Silvestrelli, Maurizio; Pascucci, Luisa
Abstract : Background . Equine adipose-derived mesenchymal stromal cells (e-AdMSC) exhibit attractive proregenerative properties strongly related to the delivery of extracellular vesicles (EVs) that enclose different kinds of molecules including RNAs. In this study, we investigated small RNA content of EVs produced by e-AdMSC with the aim of speculating on their possible biological role. Methods . EVs were obtained by ultracentrifugation of the conditioned medium of e-AdMSC of 4 subjects. Transmission electron microscopy and scanning electron microscopy were performed to assess their size and nanostructure. RNA was isolated, enriched for small RNAs (<200 nt), and sequenced by Illumina technology. After bioinformatic analysis with state-of-the-art pipelines for short sequences, mapped reads were used to describe EV RNA cargo, reporting classes, and abundances. Enrichment analyses were performed to infer involved pathways and functional categories. Results . Electron microscopy showed the presence of vesicles ranging in size from 30 to 300 nm and expressing typical markers. RNA analysis revealed that ribosomal RNA was the most abundant fraction, followed by small nucleolar RNAs (snoRNAs, 13.67%). Miscellaneous RNA (misc_RNA) reached 4.57% of the total where Y RNA, RNaseP, and vault RNA represented the main categories. miRNAs were sequenced at a lower level (3.51%) as well as protein-coding genes (1.33%). Pathway analyses on the protein-coding fraction revealed a significant enrichment for the "ribosome" pathway followed by "oxidative phosphorylation." Gene Ontology analysis showed enrichment for terms like "extracellular exosome, " "organelle envelope, " "RNA binding, " and "small molecule metabolic process." The miRNA target pathway analysis revealed the presence of "signaling pathways regulating pluripotency of stem cells" coherent with the source of the samples. Conclusion . We herein demonstrated that e-AdMSC release EVs enclosing different subsets of small RNAs that potentially regulate a number of biological processes. These findings shed light on the role of EVs in the context of MSC biology.